The long-term safety and efficacy of vestronidase alfa, rhGUS enzyme replacement therapy, in subjects with mucopolysaccharidosis VII - Wang, Raymond Y. (2020)
Vestronidase alfa (recombinant human beta-glucuronidase) is an enzyme replacement therapy (ERT) for Mucopolysaccharidosis (MPS) VII, a highly heterogeneous, ultra-rare disease. Twelve subjects, ages 8-25 years, completed a Phase 3, randomized, placebo-controlled, blind-start, single crossover study (UX003-CL301; NCT02377921), receiving 24-48 weeks of vestronidase alfa 4 mg/kg IV. All 12 subjects completed the blind-start study, which showed significantly reduced urinary glycosaminoglycans (GAG) and clinical improvement in a multi-domain responder index, and enrolled in a long-term, open-label, extension study (UX003-CL202; NCT02432144). Here, we report the final results of the extension study, up to an additional 144 weeks after completion of the blind-start study. Three subjects (25%) completed all 144 weeks of study, eight subjects (67%) ended study participation before Week 144 to switch to commercially available vestronidase alfa, and one subject discontinued due to non-compliance after receiving one infusion of vestronidase alfa in the extension study. The safety profile of vestronidase alfa in the extension study was consistent with observations in the preceding blind-start study, with most adverse events mild to moderate in severity. There were no treatment or study discontinuations due to AEs and no noteworthy changes in a standard safety chemistry panel. Out of the eleven subjects who tested positive for anti-drug antibodies at any time during the blind-start or extension study, including the baseline assessment in the blind-start study, seven subjects tested positive for neutralizing antibodies and all seven continued to demonstrate a reduction in urinary GAG levels. There was no association between antibody formation and infusion associated reactions. Subjects receiving continuous vestronidase alfa treatment showed a sustained urinary GAG reduction and clinical response evaluated using a multi-domain responder index that includes assessments in pulmonary function, motor function, range of motion, mobility, and visual acuity. Reduction in fatigue was also maintained in the overall population. As ERT is not expected to cross the blood brain barrier, limiting the impact on neurological signs of disease, and not all subjects presented with neurological symptoms, outcomes related to central nervous system pathology are not focused on in this report. Results from this study show the long-term safety and durability of clinical efficacy in subjects with MPS VII with long-term vestronidase alfa treatment.